Use of statins to control hyperlipidemia after kidney transplantation: associated factors and possible benefits in a narrative review - Freitas, Cícero Alexandre de; Alcântara Neto, José Martins de; Andrade, Cinthya Cavalcante de; Oliveira, Alene Barros de (Brazilian Journal of Transplantation, 2021)
Preservation of graft function is the major concern in the follow-up of kidney transplant recipients. In contrast, those patients are subjected to cardiovascular disease, hypertension, dyslipidemia, diabetes mellitus, adverse effects of immunosuppressant drugs with altered lipoprotein levels and other metabolic disorders, which can contribute to graft loss and increased morbidity and mortality. Lipid lowering therapy with statins can offer protection to the renal graft endothelium, with consequently decreased rejection rates and improved quality of life. The present study aimed to approach the use of statins as lipid-lowering therapy in kidney transplant recipients, through a narrative review of the literature. A search was conducted on the following platforms: Pubmed, Scielo, LILACS, Cochrane Library and MedRxiv, which was followed by explanatory reading. Eleven scientific articles with the descriptors: ‘Kidney Transplantation’, ‘Hydroxymethylglutaryl-CoA Reductases Inhibitors’ and ‘Hypercholesterolemia’ were included. Of those studies, 45.6% (5) discuss the benefits of using statins to control lipid rates, 36.4% (4) describe the risks and benefits of using statins for damage progression, and 18% (2) report the effectiveness of statins associated with other drugs. The use of Hydroxymethylglutaryl-CoA Reductase Inhibitors (statins) has clinical relevance in kidney transplant recipients, with the main purpose to lowering the lipid levels, thus increasing the safety of treatment and promoting benefits for kidney transplant recipients.